ANALISIS PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP PENGEMBANGAN KARIR PADA SEKOLAH STAF DAN PIMPINAN POLRI DI LEMBANG BANDUNG - Karnama, Maman Mulya (LPPM Universitas Buana Perjuangan Karawang, 2016)
ABSTRACT The purpose of this study was to obtain empirical evidence and found the clarity of the phenomenon and conclusions about the influence of education and training (training) and motivation for career development at the School of Police Staff and Leaders in Lembang, Bandung. The study was conducted by using a quantitative method with descriptive analysis and verification methods, namely; collecting, presenting, analyzing and testing hypotheses, and make conclusions and suggestions. Based on the results of the analysis of the results, we concluded as follows: The implementation of education and training (training) are on a scale of good, it means that education and training (training) is in conformity with the program. Implementation of career development is on a scale of good, it means that the career development has been implemented properly. Effect of education and training (training) have a significant influence on career development. Based on the results of educational research and training (training) is dominant to contribute to the career development. Keywords: education and training (training), career development